Identification and estimation of marginal effects in nonlinear panel models - Victor Chernozhukov; Iván Fernández-Val; Jinyong Hahn; Whitney Newey (Centre for Microdata Methods and Practice (cemmap), 2008)
This paper gives identification and estimation results for marginal effects in nonlinear panel models. We find that linear fixed effects estimators are not consistent, due in part to marginal effects not being identified. We derive bounds for marginal effects and show that they can tighten rapidly as the number of time series observations grows. We also show in numerical calculations that the bounds may be very tight for small numbers of observations, suggesting they may be useful in practice. We give an empirical illustration.
Keywords: 330; Nichtlineares Verfahren; Präferenztheorie; Marginalanalyse